2022
DOI: 10.3390/microorganisms10102089
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Endophytic Bacteria of Leucojum aestivum ‘Gravety Giant’ as a Potential Source of Alkaloids and as Antagonist to Some Plant Fungal Pathogens

Abstract: Leucojum aestivum is a medicinal plant belonging to the Amaryllidaceae family well known as a producer of alkaloids such as galanthamine and lycorine. However, the endophytic microbes that colonize different plant tissues without causing any damage have not been reported in this plant. Here, we explored the different endophytic bacterial communities isolated from different surface disinfected tissues of L. aestivum ‘Gravety giant’ and screened bacterial isolates producing alkaloids and their potential use as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…All the isolates showed the presence of alkaloids (Figure 5A1-5A7). The presence of alkaloids in bacteria has also been reported in previous studies by Purwestri et al (2016), Munakata et al (2022), andPtak et al (2022). Alkaloid is a nitrogen base compound that poses numerous health benefits.…”
Section: Phytochemical Testsupporting
confidence: 63%
“…All the isolates showed the presence of alkaloids (Figure 5A1-5A7). The presence of alkaloids in bacteria has also been reported in previous studies by Purwestri et al (2016), Munakata et al (2022), andPtak et al (2022). Alkaloid is a nitrogen base compound that poses numerous health benefits.…”
Section: Phytochemical Testsupporting
confidence: 63%
“…More bacterial endophyte isolates found in roots indicate that roots provide a more favorable environment for bacterial colonization. Earlier studies also reported that the number of endophytic bacteria in roots of Leucojum aestivum [14], Lactuca indica [15], and Targetes sp. [16], was higher than aerial plant parts.…”
Section: Endophytic Bacteria Isolated From M Fatua and Their Antibact...mentioning
confidence: 78%
“…The traditional screening of alkaloid-producing strains is usually carried out via alkaloids detecting in culture extracts by chromogenic reactions in liquid or on TLC plate and by HPLC, LC-MS, or direct ESI-MS ( Yin and Sun, 2011 ; Han et al, 2015 ; da Silva et al, 2021 ; Munakata et al, 2022 ). However, these methods usually require a term of fermentation before extraction of metabolites from all the tested strains in the first step.…”
Section: Discussionmentioning
confidence: 99%
“…However, in situ colony screening of alkaloidproducing strains has not been reported. The traditional screening of alkaloid-producing strains is performed by fermentation of all the tested strains, metabolites extraction, preliminary thin-layer chromatographic (TLC) colorization analysis using dyes like Dragendorff reagent, and in-depth diversity analysis using high performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC-MS), or direct compound isolation and structural elucidation (Yin and Sun, 2011;Han et al, 2015;Munakata et al, 2022). This pipeline is laborious, time-consuming, long-period, and unpredictable to the structural information.…”
Section: Introductionmentioning
confidence: 99%